Suprachoroidal space-inducing hydrogel-forming microneedles (SI-HFMN): An innovative platform for drug delivery to the posterior segment of the eye - Jaibyung Choi; Suhyeon Shim; Jiwoo Shin; Ahhyun Lee; Jaan Strang; Tobias Braun; Reto Naef; Hyungil Jung (Bioactive Materials)
The suprachoroidal space (SCS), which exists between the sclera and choroid, offers a promising delivery route to the posterior segment of the eye (PSE) and is integrated with hollow microneedles (HMNs) for minimally invasive delivery. However, HMNs are limited by backflow owing to their narrow channel. Therefore, this study proposes a biocompatible SCS-inducing hydrogel-forming microneedle (SI-HFMN) with a specially designed candlelit shape that swells to separate the sclera from the choroid. The induced SCS provides a route for delivering loaded drugs to the PSE upon application. The optimized formulation of 20 % (w/w) poly(methyl vinyl ether-alt-maleic acid) (PMVE/MA) crosslinked with 7.5 % (w/w) polyethylene glycol (PEG) possesses sufficient mechanical strength (5.1 ± 0.7 N) to penetrate both the sclera and swell by 356 ± 28 %, to mechanically stimulate SCS formation. The formulation also recorded a drug absorption amount of 101 ± 9 μg/mg of hydrogel. Furthermore, in vitro and ex vivo experiments demonstrated the ability of the SI-HFMN to deliver drugs to the PSE via the formed SCS. Thus, this system offers an innovative method for drug delivery to PSE by inducing SCS formation.